The Causal Relationship between Fuel Consumption, Exchange Rates and Economic Growth in South East Sulawesi, Indonesia - Rahim, Manat; Adam, Pasrun; Millia, Heppi; Suriadi, La Ode; Saidi, La Ode Ode (International Journal of Energy Economics and Policy, 2021)
This article reports the results of a study examining the causal relationship between fuel consumption, exchange rates, and economic growth in Southeast Sulawesi, Indonesia. The data used are annual time series data ranging from 1988 to 2016. The estimation results of the VAR model and the Granger causality test indicate that the causal relationship that occurs is only a short-term causality, namely from fuel consumption to economic growth. Keywords: fuel consumption, exchange rate, economic growth, VAR model, Granger causality test. JEL Classifications: C120, C320, E21, F31 DOI: https://doi.org/10.32479/ijeep.11518